Bionic Cooling Skin for Infected Wound Healing - Shi, Shuo; Zhou, Huiqun; Ming, Yang; Zhou, Xiong; Wu, Hanbai; Ren, Haipeng; Chow, Lung; Su, Jing; Chen, Daming; Fei, Bin; Razal, Joselito M.; Wang, Xungai (Nano-Micro Letters, 2026)
Infected wounds can lead to delayed healing, suppuration, and potentially life-threatening complications, making their management critically important. An ideal wound dressing should possess key characteristics such as high protective function, comfortable user experience, and effective antibacterial efficiency. However, a single dressing that integrates all these functions is rarely achieved. Herein, we developed a “bionic cooling skin” for infected wound management based on hierarchical nanofiber construction. This was achieved by integrating solvent welding technology with single-sided metal–organic frameworks (MOFs) that generate visible light-responsive reactive oxygen species (ROS, band gap = 2.56 eV). The designed bionic skin promotes rapid healing of infected wounds, and the healing mechanism has been confirmed by gene analysis. This advanced dressing closely mimics natural skin, exhibiting similar mechanical properties (σmax = 21.6 MPa; εmax = 54%), and high air and moisture permeability (> 1.8 mL s−1 and > 12.5 kg m−2 d−1), respectively. Furthermore, the bionic cooling skin reduces the local temperatures of wounds exposed to sunlight by 4 °C, mitigating heat gain through high mid-infrared emissivity. This innovative bionic wound dressing not only enhances comfort and healing efficacy but also advances our understanding of wound repair mechanisms, holding significant promise for future wound care and biomedical material design. Highlights: 1 A bionic cooling skin with a hierarchical Janus nanofiber structure was fabricated by combining solvent welding technology with single-sided visible light-responsive metal–organic frameworks. 2 This unique design simultaneously realized effective passive cooling ( 4 °C reduction under sunlight) through high mid-infrared emissivity and on-demand antibacterial activity via photocatalytic reactive oxygen species generation. 3 The bionic skin dressing closely mimics natural skin in mechanical properties and permeability while demonstrating superior healing performance for infected wound, with mechanistic insights supported by comprehensive gene expression analysis.